Dreams Interpretation of The Main Character in A Monster Calls Movie Directed By J.A. Bayona - Unpris Yastanti; Retno Ameliani (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The purpose of this analysis is to identify dream interpretation of the main character, Conor O’Malley in A Monster Calls movie directed by J.A. Bayona. The method of this analysis is descriptive qualitative method. Sigmund Freud’s theory is used to analyze. The results of this research show that: (1)The interpretation of dream and the three stories in dream of main character are related to conflict that experienced by Conor.(2) The type of dream experienced by Conor is nightmare. Conor's  nightmare is a reaction to the illness suffered by his mother.